El culto a Mitra en la época de Caracalla - Aguado García, Paloma (Gerión. Revista de Historia Antigua, 2001)
The ancient tradition has established that the severan age existed an anormous develoment of Mitras`s cult in the imperial court. However we cant state that with regard to the present documentation, Mitras was a simply god among others in Emperor Caracalla`s preferences.